Area of effective catch of crab traps in the northwestern part of the Tartar Strait - Vladimir I. Ostrovsky; Olga B. Tkacheva; Alexander V. Kharitonov; Vitaly N. Shalenko (Известия ТИНРО, 2014)
Japanese cone-shaped traps for crabs are calibrated with the data of trawl survey in the northwestern Tartar Strait. The 100 % effective catch area for each trap in the order does not exceed 665 m2 for spiny crab, 1513 m2 for king crab, 3811 m2 for horsehair crab, and 4019 m2 for tanner crab opilio. Unification of methods for the stock assessment by trap surveys is discussed.